Endolysosomal Ca2+ Signaling in Cancer: The Role of TPC2, From Tumorigenesis to Metastasis - Alharbi, Abeer F.; Parrington, John (Frontiers in Cell and Developmental Biology, 2019)
Ca2+ homeostasis is dysregulated in cancer cells and affects processes such as tumorigenesis, angiogenesis, autophagy, progression, and metastasis. Emerging evidence has suggested that endolysosomal cation channels sustain several cancer hallmarks involving proliferation, metastasis, and angiogenesis. Here, we investigate the role of TPC1-2, TRPML 1-3, and P2X4 in cancer, with a particular focus on the role of TPC2 in cancer development, melanoma, and other cancer types as well as its endogenous and exogenous modulators. It has become evident that TPC2 plays a role in cancer; however, the precise mechanisms underlying its exact role remain elusive. TPC2 is a potential candidate for cancer biomarkers and a druggable target for future cancer therapy.